Pelatihan Manajemen Materi dan Aktivitas di LMS SYAM-OK untuk Dosen Fakultas Teknik Universitas Negeri Makassar - Mawarni, Sella; Rais, Muhammad; Hartoto; Yanti, Nur Eva; Syah, Maenuddin Bustanil (LOSARI DIGITAL, 2025)
LMS SYAMOK is an online learning platform (e-learning) at Universitas Negeri Makassar used by lecturers and students to support the implementation of the blended learning model. The partner in this training activity is the Faculty of Engineering, Makassar State University. This training activity focuses on material management and activity management activities in the LMS. Material management is related to the management of materials in the LMS which includes identifying the type of material or learning object material (LOM) that suits the characteristics of students and developing material content in the format of modules, infographics, and interactive videos. Activity management is related to LMS activities that can be used to assess student understanding after learning through the material in the LMS. Activities can be in the form of quizzes, discussion forums, and assignments. The methods used in this training activity are in the form of material presentations, tutorials, discussions, and guided practice. The presentation of the material is presented at the beginning of the training to provide a foundation for concepts related to material management and activities in the LMS. In the guided practice session, training participants are taught to fill in 1 meeting in the SYAM-OK class completely consisting of material content and activities that are relevant to the topic of the material. The results of the evaluation of the training activities show an increase in lecturer competence in developing online classes in the SYAM-OK LMS.